Casas comerciales y circuitos mercantiles Antioquia: 1842-1880 - Botero Restrepo, María Mercedes (Sociedad y Economía, 2007)
In the 1850s, Antioquia started showing significant commercial development resultingmostly from gold-mining expansión. New mining sites and colonization generated newmarkets; commercial organizations gained importance and extended abroad.Based on the archives of commercial houses of the time, this essay contributes to studies of19* century commerce by describing trade, commercial-instruments, geographical áreascovered by merchants, and trade networks that joined small localities with cities and foreignmarkets.